2008
DOI: 10.2352/j.imagingsci.technol.(2008)52:4(040908)
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating the Yule–Nielsen Modified Spectral Neugebauer Model with Ink Spreading Curves Derived from Digitized RGB Calibration Patch Images

Abstract: The Yule-Nielsen modified spectral Neugebauer model (YNSN) enhanced for accounting for ink spreading in the different ink superposition conditions requires a spectrophotometer to measure the reflectances of halftone calibration patches in order to compute the ink spreading curves mapping nominal ink surface coverage to effective ink surface coverage. Instead, as a first step towards the "on the fly" characterization of printers, we try to deduce the ink spreading curves from digitized RGB images of halftone ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Color prediction models have been successfully applied to color reproduction management [5][6][7][8][9]. Their major drawback is that all of them are computationally capacious, as colorants require a solution of system of equations; therefore, they might be barely implicated into a real workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Color prediction models have been successfully applied to color reproduction management [5][6][7][8][9]. Their major drawback is that all of them are computationally capacious, as colorants require a solution of system of equations; therefore, they might be barely implicated into a real workflow.…”
Section: Introductionmentioning
confidence: 99%
“…The color prediction models have been successfully applied to the color reproduction management [5][6][7][8][9], however, all the proposed approaches require a significant number of measurements, computations and checks. However, since most of them are based on empirical relationships, the accuracy of predicting some shades of the reflection spectrum remains low.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches are reported in the literature to separately characterize physical and optical dot gain. Garg et al [30], Hebert and Hersch [45], Yang and Lundström [119] used transmittance and reflectance value measurement to estimate the physical dot gain e↵ect. Koopipat et al [61] and Yamashita et al [116] have reported that the reflected images are images that include both physical and optical dot gain, while the transmitted images only include the physical dot gain e↵ect.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works the physical and optical dot gains were mostly analyzed by illustrating their respective dot gain curves [30,45,119]. These curves only show the relationship between the e↵ective dot area and the reference (or nominal) dot area, and do not illustrate the shape of the printed dots including the e↵ect of optical dot gain, which is closely related to the optical properties of the paper and physical dot shape.…”
Section: Introductionmentioning
confidence: 99%